Review: Groundwater research in the Ethiopian Rift Valley Lakes region - Hulluka, Taye Alemayehu; Balcha, Sisay Kebede; Yohannes, Biniyam; Bantider, Amare; Negatu, Adey (Frontiers in Water, 2023)
Despite its proximity to many research institutions in the country and prevailing environmental and water security challenges, water resources research in the Central Rift Valley of Ethiopia has few decades of history. Research undertaken so far, mainly focus on the lakes' environment and anthropogenic activities in their proximities. Worsening deterioration of the water resources and environmental conditions; and the need to address overlooked but determinant natural and anthropogenic processes spurred a critical review of what has been done so far. This work provides an overview of the history of water research in the central rift valley and tries to reveal research gaps related to surface water-groundwater interaction, water quality, and changing trends in the hydro ecosystem and possible causes. Apart from this, articles dealing with the geological and structural setup of the central rift valley were systematically reviewed to show their control over the hydrologic system. The review work has revealed that although the current state of the central rift valley is a product of anthropogenic and geogenic processes; which are happening within the sub-basin and its adjacent basins that need to be addressed at a higher thematic, spatial, and temporal scopes, there is gap in reviewed research, to address the issue at this level. The forefront environmental challenges and the need for quick fixes, lack of data, and funding are found to be some of the reasons to limit the scope of research activities, mainly to shallow groundwater zones and surface hydrological processes around the lakes. This approach has hindered seeing the bigger picture and resulted in ineffective environmental and natural resources restoration measures and policy decisions.